2017
DOI: 10.1016/j.biocon.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of a failed offset

Abstract: Biodiversity offsetting is widely applied but its effectiveness is rarely assessed. We evaluated the effectiveness of a nest box program intended to offset clearing of hollow-bearing trees associated with a freeway the upgrade in southern Australia. The offset targeted three threatened vertebrates: squirrel glider (Petaurus norfolcensis), brown treecreeper (Climacteris picumnus) and superb parrot (Polytelis swainsonii). Clearing led to the loss of 587 tree hollows and the offset was the placement of an equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 32 publications
(20 reference statements)
2
138
1
Order By: Relevance
“…For example, long-term monitoring of bat boxes in Melbourne, Australia has shown that, despite the provision of boxes constructed from materials with a range of insulative properties (ranging from 12 mm plywood to 90 mm pine), box use was dominated by one widespread, urban-adapted species, Gould's wattled bat Chalinolobus gouldii (Gray, 1841) [71]. Further research is required to investigate whether there is a link between the thermal profiles in nest boxes (compared to tree hollows) deployed in disturbed landscapes and their disproportionate level of use by widespread, highly adaptable species of birds [29,93,94] and mammals [21,71,95,96]. Field-based studies examining rates of occupation of chainsaw hollows and log hollows by target species versus undesirable exotic species would be of great interest, particularly in urban and peri-urban landscapes where nest box programs are often undertaken by land managers and conservation-focused community groups [4,97].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, long-term monitoring of bat boxes in Melbourne, Australia has shown that, despite the provision of boxes constructed from materials with a range of insulative properties (ranging from 12 mm plywood to 90 mm pine), box use was dominated by one widespread, urban-adapted species, Gould's wattled bat Chalinolobus gouldii (Gray, 1841) [71]. Further research is required to investigate whether there is a link between the thermal profiles in nest boxes (compared to tree hollows) deployed in disturbed landscapes and their disproportionate level of use by widespread, highly adaptable species of birds [29,93,94] and mammals [21,71,95,96]. Field-based studies examining rates of occupation of chainsaw hollows and log hollows by target species versus undesirable exotic species would be of great interest, particularly in urban and peri-urban landscapes where nest box programs are often undertaken by land managers and conservation-focused community groups [4,97].…”
Section: Discussionmentioning
confidence: 99%
“…Nest boxes are a popular tool for providing supplementary habitat for hollow-dependent fauna in disturbed landscapes where natural hollows are limited [4,21]. However, traditional plywood or timber nest boxes are not effective at replicating the thermal conditions that occur within natural tree hollows [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations